2020
DOI: 10.1371/journal.pone.0230136
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E mutational load as a prognosis biomarker in malignant melanoma

Abstract: Analyzing the mutational load of driver mutations in melanoma could provide valuable information regarding its progression. We aimed at analyzing the heterogeneity of mutational load of BRAF V600E in biopsies of melanoma patients of different stages, and investigating its potential as a prognosis factor. Mutational load of BRAF V600E was analyzed by digital PCR in 78 biopsies of melanoma patients of different stages and 10 nevi. The BRAF V600E load was compared among biopsies of different stages. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In recent years, controversial results have been obtained by studies which related the BRAF V600E MAF of melanoma tumors with clinicopathological and prognostic characteristics as well as the melanoma response, in order to target therapies [15,[23][24][25][26]. All these studies analyzed the MAF value of one specific region for each tumor, so we wanted to know whether the variation degree of BRAF V600E MAF within different regions of the same tumor could influence these characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, controversial results have been obtained by studies which related the BRAF V600E MAF of melanoma tumors with clinicopathological and prognostic characteristics as well as the melanoma response, in order to target therapies [15,[23][24][25][26]. All these studies analyzed the MAF value of one specific region for each tumor, so we wanted to know whether the variation degree of BRAF V600E MAF within different regions of the same tumor could influence these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the usefulness of the BRAF V600E driver mutation as a therapeutic target, a recent study has suggested that the mutational load of BRAF V600E is a possible prognostic biomarker [15], expanding the classical histopathological prognostic criteria such as ulceration, Breslow, Clark or mitotic indexes [1,[16][17][18][19][20][21][22]. Moreover, some studies in recent years have attempted to relate the mutational load to the response in order to target therapies, but controversial results have been obtained [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with BRAF mutation, the ideal sequence of treatment or the choice of sequence of combination is still an open issue [4,31,98]. The results of two large ongoing studies are awaited.…”
Section: Combination Immunotherapy Studies Have Revealed That the Pomentioning
confidence: 99%
“…In 2005, Uhara et al reported an elevate detection of the BRAF mutation in patients with melanoma without chronic sun-induced damage [ 28 , 29 ]. Further research showed that nearly 40-50% of cutaneous melanomas have mutations in BRAF, a gene that belongs to the family of mitogen activated protein kinase (MAPK) and codes for a serine/threonine protein kinase constituting part of RAS-RAF-MEK [ 30 , 31 ]. BRAF activation induces the phosphorylation of extracellular signal-regulated kinases (ERK) that constitute the most common mutated isoforms in cancer [ 32 ].…”
Section: Metastatic Melanomamentioning
confidence: 99%
“…Other biomolecules besides SVN are already used extensively as biomarkers for cancer prediction or prognosis. Well-known examples include EGFR in molecular apocrine breast cancer (MABC) [69], VEGF in colorectal cancer [70] and oncogenic BRAF mutation [71] and KRAS mutations in pancreatic cancer [72]. Since SVN is also upregulated in autoimmunity and inflammation, for tumor diagnosis, it is necessary to combine an SVN test with other biomarkers.…”
Section: Combination Of Svn Test With Other Biomarkersmentioning
confidence: 99%